Publisher Correction: Immunoprophylactic and immunotherapeutic control of hormone receptor-positive breast cancer - Buqué, Aitziber; Bloy, Norma; Perez-Lanzón, Maria; Iribarren, Kristina; Humeau, Juliette; Pol, Jonathan G; Levesque, Sarah; Mondragon, Laura; Yamazaki, Takahiro; Sato, Ai; Aranda, Fernando; Durand, Sylvère; et al. (Nature communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.